2012
DOI: 10.1158/0008-5472.can-11-3928
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Drugs Synergize with 2-Deoxyglucose to Trigger Breast Cancer Cell Death

Abstract: Cancer cells are long known to exhibit increased aerobic glycolysis, but glycolytic inhibition has not offered a viable chemotherapeutic strategy in part due to the systemic toxicity of antiglycolytic agents. However, recent studies suggest that a combined inhibition of glycolysis and mitochondrial function may help overcome this issue. In this study, we investigated the chemotherapeutic efficacies of mitochondria-targeted drugs (MTDs) in combination with 2-deoxy-D-glucose (2-DG), a compound that inhibits glyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
269
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(282 citation statements)
references
References 46 publications
11
269
1
1
Order By: Relevance
“…An enhanced antioxidant capacity allows cancer cells to not a universal finding, and mitochondrial respiration impairment is not a fixed feature of cancer cells [41] . Although the glycolytic inhibitors targeting the Warburg effect have been investigated in various cancer types, the glycolytic inhibitors with the exception of 3-BP (a lactate analog) [18,19, , 3-BrOP (a 3-bromopyruvate derivative) [71][72][73][74] , and dichloroacetate (DCA) have demonstrated low efficacy in arresting tumor growth when used alone [99] ; these inhibitors include 2-deoxy-D-glucose (a glucose analog) [70,[100][101][102][103][104][105][106][107][108][109][110][111][112] , lonidamine (a derivative of indazole-3-carboxylic acid) [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] , methyl jasmonate on HK , 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one on PFK [162]…”
Section: Initiation Of Metastasismentioning
confidence: 99%
“…An enhanced antioxidant capacity allows cancer cells to not a universal finding, and mitochondrial respiration impairment is not a fixed feature of cancer cells [41] . Although the glycolytic inhibitors targeting the Warburg effect have been investigated in various cancer types, the glycolytic inhibitors with the exception of 3-BP (a lactate analog) [18,19, , 3-BrOP (a 3-bromopyruvate derivative) [71][72][73][74] , and dichloroacetate (DCA) have demonstrated low efficacy in arresting tumor growth when used alone [99] ; these inhibitors include 2-deoxy-D-glucose (a glucose analog) [70,[100][101][102][103][104][105][106][107][108][109][110][111][112] , lonidamine (a derivative of indazole-3-carboxylic acid) [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] , methyl jasmonate on HK , 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one on PFK [162]…”
Section: Initiation Of Metastasismentioning
confidence: 99%
“…Nonetheless, combined treatment with 2DG and afatinib in the in vivo xenograft model showed more potent antitumor activity than that in in vitro. Although cancer cells exhibit increased glycolysis and depend more on this pathway for ATP generation, the inhibition of glycolysis alone is not sufficient to effectively kill the malignant cells, like monotherapy with glycolysis inhibitors including 2DG do not show antitumor activity in in vivo xenograft studies (17,42). It has been suggested that ATP depletion should reach certain thresholds to trigger cell death by apoptosis or necrosis (43).…”
Section: Afatinibmentioning
confidence: 99%
“…9 Additionally, several recent studies have shown that simultaneous inhibition of glycolysis and mitochondrial respiration can act synergistically to reduce tumor cell survival in vitro and in vivo. [12][13][14] With respect to sarcomas, 2-DG induces apoptosis in human aRMS, but not eRMS, cell lines and inhibits osteosarcoma tumor growth (in combination with doxorubicin) and metastasis, although the mechanism and contribution of effects on cellular bioenergetics are not well-characterized. 5,15,16 Here, we describe the cellular bioenergetics of a panel of human RMS and osteosarcoma cell lines and examine the relationships between bioenergetic properties and sensitivity to metabolic inhibitors.…”
mentioning
confidence: 99%